Phase II study of temozolomide and topotecan (TOTEM) in children with relapsed or refractory extracranial and central nervous system tumors including medulloblastoma with post hoc Bayesian analysis: A European ITCC study. Issue 1 (8th October 2019) - Le Teuff, Gwénaël; Castaneda‐Heredia, Alicia; Dufour, Christelle; Jaspan, Timothy; Calmon, Raphael; Devos, Annick; McHugh, Kieran; Leblond, Pierre; Frappaz, Didier; Aerts, Isabelle; Zwaan, Christian M.; Ducassou, Stéphane; et al.
Abstract: Aim: To assess objective response after two cycles of temozolomide and topotecan (TOTEM) in children with refractory or relapsed miscellaneous extracranial solid and central nervous system (CNS) tumors, including medulloblastoma and primitive neuroectodermal tumors (PNET). Procedure: Multicenter, nonrandomized, phase 2 basket trial including children with solid tumors, completed by a one‐stage design confirmatory cohort for medulloblastoma, and an exploratory cohort for PNET. Main eligibility criteria were refractory/relapsed measurable disease and no more than two prior treatment lines. Temozolomide was administered orally at 150 mg/m 2 /day followed by topotecan at 0.75 mg/m 2 /day intravenously for five consecutive days every 28 days. Tumor response was assessed every two cycles according to WHO criteria and reviewed independently. Results: Thirty‐two patients were enrolled and treated in the miscellaneous solid tumor and 33 in the CNS strata; 20 patients with medulloblastoma and six with PNET were included in the expansion cohorts. The median age at inclusion was 10.0 years (range, 0.9‐20.9). In the basket cohorts, confirmed complete and partial responses were observed in one glioma, four medulloblastoma, and one PNET, leading to the extension. The overall objective response rate (ORR) in medulloblastoma was 28% (95% CI, 12.7‐47.2) with 1/29 complete and 7/29 partial responses, those for PNET 10% (95% CI, 0.3‐44.5). Post hoc Bayesian analysis estimates that the true ORR in medulloblastoma is probably between 20% and 30% and below 20% in PNET. The most common treatment‐related toxicities of the combination therapy were hematologic. Conclusions: Temozolomide‐topotecan results in significant ORR in children with recurrent and refractory medulloblastoma with a favorable toxicity profile.